The Problem of Literary Education for Pupils of Elementary School - Roksolana Zharkova (Vasyl Stefanyk Precarpathian National University, 2017)
The author analyzes the problem of literary education of elementary school students in the contemporary cultural space. The article states that the literary education based on literary Propedevtics of younger students and is based on the process of reading fiction. Therefore, it is important to promote reading, promote children's reading and children's book production in Ukraine. The author concludes that the gradual renewal of the education system, particularly literary education of primary school children should be primarily seen in the development of new textbooks and anthologies that will meet the needs and opportunities of the modern child.